Structural strengthening mitigation through protection cathodic (Research, Society and Development, 2020)
Concrete is the construction material most used in civil construction by humanity. In the last century, with acceleration after the second world war. its development provided the growth of cities, with the increase of bold structures of simple plasticity, which seem to unravel the law of gravity. Paradoxically, it has not always received the necessary attention to its durability and conservation. Several methods have been consolidated for use in its repair and maintenance, creating a specific aspect in engineering for its use, where, however, all prove to be expensive and expensive. Used for decades in the shipbuilding industry, cathodic protection still has restricted use in construction, representing a huge advance in the maintenance of concrete or reinforced mortar structures. It has the advantage of being able to be inserted at any time during the life of the structure, although it must be foreseen from the initial stage of the project. The incorporation into existing structures provides the extension of its useful life, reduction of the cost of maintenance, recovery or reinforcement in more extreme cases.